Are you asking what 6 times 4 is?
Answer:
24
Answer:
Step-by-step explanation:
Can u give me thanks I need it so I can get 50 points plz
Answer:
x = 2
Step-by-step explanation:
6x-1=11
Add 1 to each side
6x-1+1=11+1
6x = 12
Divide by 6
6x/6 = 12/6
x = 2
You take the first equation and make a value for y. So 6x + y =7 change it to :
y = -6x + 7
Now in the second equation replace the “y” with -6x +7 this is what it means to use substitution method . Your combined equation will now be :
8x + 9(-6x + 7) =17
Now do distributive property and you get :
8x + -54x +63 =17
Now combine like terms ;
-46x +63 =17
-46x =-46
x = 1
Now replace 1 for X value and we can get the value of Y .
Y=1
X=1
Answer:
Really? Oof XD You really must be bored then
Step-by-step explanation:
Wanna talk?
Have a nice day!! <3